2019
DOI: 10.1108/cdi-03-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and career success: the effects of career skills and proactive personality

Abstract: Purpose The purpose of this paper is to examine the effect of servant leadership on followers’ subjective career success and the mediating role of career skills. The moderating effect of followers’ proactive personality is also investigated. Design/methodology/approach This paper collected two-wave matched data from 283 employees of an IT company. The authors use hierarchical regression and bootstrapping to test the hypotheses. Findings Servant leadership has a positive effect on career satisfaction and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…Indeed, recent well-being literature suggests a close link between pro-activity and SWB. Wang et al (2019) show pro-active personality is positively related to life satisfaction in general. Jawahar and Liu (2017) also find that pro-active people are more satisfied with their jobs, career, and life in general (c.f., Prabhu, 2007;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…Indeed, recent well-being literature suggests a close link between pro-activity and SWB. Wang et al (2019) show pro-active personality is positively related to life satisfaction in general. Jawahar and Liu (2017) also find that pro-active people are more satisfied with their jobs, career, and life in general (c.f., Prabhu, 2007;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…The review is based on “Servant leadership and career success: the effects of career skills and proactive personality” by Wang et al . (2019), published in “Career Development International.” This research paper explores the link between servant leadership and the subjective career success of employee followers.…”
Section: Commentarymentioning
confidence: 99%
“…Ancient Chinese philosopher Lao Tzu summarized his advice on effective leadership in the pithy phrase, “to lead people, walk behind them.” A research paper by Wang et al . (2019) concentrates on how servant leadership within an organization impacts the subjective career success of an employee who follows that leader.…”
mentioning
confidence: 99%
“…This will encourage graduates to further develop other skills and capabilities to facilitate their transition into early career in the hotel. However, there has been an increase interest in validating the involvement of HEI in developing skills and competencies of graduates towards their early career in the hotel (Chang & Busser, 2020;Gebbels et al, 2020;Wang et al, 2019). Recent studies indicated that the increase was mainly attributed by fresh graduates' lack of commitment, competence and personality (Haldorai et al, 2019;Han, 2020;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%